Penyuluhan Pola Hidup Sehat Dengan Mengonsumsi Ikan Setiap Hari Di MTs Ikhlaashul ‘Amal Sebawi: Counseling on Healthy Lifestyles By Consuming Fish Every Day at MTs Ikhlaashul 'Amal Sebawi - Idris; Erma Tantilia; Lassram Bulano; Muhammad Syafiq (Pakis Journal Institute, 2022)
Fish is a source of high-quality protein that has a positive effect on the body. Fish protein is more easily absorbed when the required amino acid composition and quantity are complete. higher than beef, chicken and other meats. This is because fish is considered a superfood due to its high protein content and omega-3 fatty acids. The purpose of this counseling is to provide knowledge about healthy lifestyles by consuming fish every day to MTs Ikhlaashul'Amal students. The method used in this counseling is by lectures with material exposure and evaluation. Students are very enthusiastic about the material presented by listening to the material to the end and discussion at the end of the material so that two-way communication occurs. The results of counseling that students are increasing their understanding of a healthy lifestyle by eating fish every day.